Optimizing the synergy between alloy and alloy–oxide interface for CO oxidation in bimetallic catalysts. Issue 19 (9th May 2022) - Pan, Ya; Xu, Liuxin; He, Wenxue; Li, Hongmei; Chen, Wei; Sun, Zhihu
Abstract : An optimized synergy between alloy and alloy-oxide in Pt–Co/Al2 O3 bimetallic catalysts for CO oxidation. Abstract : Creating synergetic metal–oxide interfaces is a promising strategy to promote the catalytic performance of heterogeneous catalysts. However, this strategy has been mainly applied to monometallic catalysts, while scarcely applied to alloy catalysts. In this work, we present a comprehensive study on the synergetic alloy–oxide interfaces in the bimetallic Pt–Co/Al2 O3 catalysts for CO oxidation. A series of Pt1 Co x /Al2 O3 catalysts with various Co/Pt molar ratios with x ranging from 0.5 to 3.8 was synthesized via a facile wet-chemistry strategy. Among them, the Pt1 Co0.5 /Al2 O3 catalyst exhibits the best catalytic performance for CO oxidation, with the lowest CO complete conversion temperature of −10 °C and the highest mass specific rate of 2.61 (mol CO) h −1 (g Pt) −1 . From in situ X-ray absorption fine structure and diffuse reflectance infrared Fourier-transform spectroscopy studies, the superior catalytic performance of Pt1 Co0.5 /Al2 O3 originates from the optimal length of the three-dimensional alloy-oxide perimeter sites. We further extended this strategy to other bimetallic systems of Pt–Fe and Pt–Ni, which also show similar structural properties and remarkable promotional effects on the catalytic activity.